Fodder banks: For pastoralists or farmers - Mohamed-Saleem, M.A.; Suleiman, H.; Otsyina, R.M. (International Livestock Centre for Africa, 1986)
Outlines the principles and practices of fodder-bank establishment and management in the sub-humid zones of West Africa. Summarises data that indicate the benefit of fodder banks to subsequent crops.